Chronology and Eruption Dynamics of the Historic∼1700 CE Eruption of Tseax Volcano, British Columbia, Canada - Le Moigne, Yannick; Williams-Jones, Glyn; Vigouroux, Nathalie; Russell, James K. (Frontiers in Earth Science, 2022)
The ~1700 CE Tseax eruption in north-western British Columbia, is the second youngest volcanic event in Canada and is one of Canada’s worst natural disasters as it killed up to 2,000 people of the Nisga’a First Nation living there at the time, Adaawak stories preserve an observational account of the Tseax eruption. In this study, we establish the chronology of the eruption by integrating field observations, petrophysical data and Nisga’a oral and written histories. The Nisga’a stories corroborate the short duration and exceptional intensity of the eruption as recorded in the volcanic products. The eruption was divided in two main periods: (1) Period A and (2) Period B. (1) The eruption started in a typical Hawaiian style with low levels of lava fountaining that built up a spatter rampart. This pyroclastic edifice was breached by voluminous pāhoehoe lava flows erupted at high discharge rates. We estimate that almost half of the erupted flow volume (0.20 km3) erupted in Period A was fed by a flux of 800-1000 m3/s. The lava reached the Nass Valley, 20 km downstream of the volcano, in “swift currents”, diverted the Nass River and engulfed the former Nisga’a villages in only 1 to 3 days, thus likely being responsible for the reported fatalities. The discharge rates progressively diminished to 10-200 m3/s until the end of this first eruptive period, which lasted a few weeks to a few hundred days. (2) During Period B, two ‘a‘ā flows were erupted with discharge rates < 50 m3/s. This period was also characterised by an explosive phase of eruption that built a 70 m high tephra cone overlapping with spatter rampart. In total, Period B lasted approximately 20 days. In total, the eruption produced 0.5 km3 of volcanic materials (mostly in the form of lava flows) on the order of weeks to a few months. The eruption of Tseax was similar in magnitude to the flank eruption on larger shield volcanoes such as Kīlauea’s Fissure 8 in 2018 or Mauna Loa in 1984.